2017
DOI: 10.1016/j.euroneuro.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Mild White Matter Changes in Un-Medicated Obsessive-Compulsive Disorder Patients and Their Unaffected Siblings

Abstract: Objective: Obsessive-compulsive disorder (OCD) is a common neuropsychiatric disorder with moderate genetic influences and white matter abnormalities in frontal-striatal and limbic regions. Inconsistencies in reported white matter results from diffusion tensor imaging (DTI) studies can be explained, at least partly, by medication use and between-group differences in disease profile and stage. We used a family design aiming to establish whether white matter abnormalities, if present in un-medicated OCD patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…The sibling group showed intermediate FA and RD values between OCD and HC groups in the cingulum and forceps minor which are spatially in line with previous studies reporting intermediate FA values in the medial frontal regions 22 and intermediate FA and RD values in cingulum 12 in unaffected siblings of OCD patients. Furthermore, the sibling group also showed intermediate streamline numbers in all edges with significantly lower streamline counts in patients with OCD compared to HCs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The sibling group showed intermediate FA and RD values between OCD and HC groups in the cingulum and forceps minor which are spatially in line with previous studies reporting intermediate FA values in the medial frontal regions 22 and intermediate FA and RD values in cingulum 12 in unaffected siblings of OCD patients. Furthermore, the sibling group also showed intermediate streamline numbers in all edges with significantly lower streamline counts in patients with OCD compared to HCs.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, 12,14,19,20 FA differences were mainly due to increases in RD values in both OCD and sibling groups suggesting myelin‐related WM alterations. In line with this hypothesis, a recent longitudinal study in healthy adolescents and young adults reported increased compulsivity is tied to slower myelination in fronto‐striatal regions 72 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Alternatively, that subgroup analysis was insufficiently powered to detect group differences. Findings from previous TBSS studies of unmedicated OCD participants are discrepant, with one showing reduced FA in anterior corpus callosum (Nakamae et al, 2011) (i.e., forceps minor) and the other showing reduced FA in the left cingulum (Fan et al, 2016). Over half of the OCD participants included in the latter study also met criteria for one or more comorbid current axis 1 disorder, suggesting that further study of white matter microstructure in a larger sample of unmedicated OCD participants free of psychiatric comorbidities is warranted.…”
Section: Discussionmentioning
confidence: 88%